(untitled) (Trabalho & Educação, 2018)
This article results of a PhD research which objective was to define and analyze the meanings of the relationships established between education, leisure and work within the schools of professional and technological education (EPT), in Brazil, based on activities and cultural manifestations related to leisure and incorporated into the educational processes and daily life of these schools. The research was developed in two schools of the Federal Network of Professional, Scientific and Technological Education – the Technical College of UFMG and the campuses I and II of CEFET-MG, in Belo Horizonte, Minas Gerais state –, taking the materialistic dialectic as the fundamental principle of the research. Having as main source of data the reality studied within these schools, the methodological procedures took into account two interlinked research movements, necessarily integrated by spiral correlations: bibliographical and documentary research; and field research, properly speaking. In this paper, it is sought to highlight the contradictions and aspects related to cultural activities and manifestations related to leisure as part of the educational processes in the schools studied. In addition, their possible articulation to a professional formation conformed to the labor market is considered, as producer of resigned worker. At the same time it seeks to reveal the potentialities of emancipation and the quest for autonomy and freedom when these activities and manifestations are used. ___ Este artigo resulta de pesquisa de doutoramento cujo objetivo foi delimitar e analisar os significados das relações estabelecidas entre educação, lazer e trabalho no interior de escolas de educação profissional e tecnológica (EPT), com base nas atividades e nas manifestações culturais relacionadas ao lazer e incorporadas aos processos educacionais e ao cotidiano dessas escolas. A pesquisa foi desenvolvida em duas escolas da Rede Federal de Educação Profissional, Científica e Tecnológica – o Colégio Técnico da UFMG e os campi I e II do Cefet-MG, em Belo Horizonte –, tomando-se como princípio fundamental de pesquisa a dialética materialista. Buscou-se aqui, evidenciar as contradições e aspectos relacionados às atividades e manifestações culturais relacionadas ao lazer como parte dos processos educacionais nas escolas pesquisadas, considerando sua possível articulação a uma formação profissional conformada ao mercado de trabalho, produtora de um trabalhador resignado. Ao mesmo tempo em que se busca revelar as potencialidades de emancipação e de busca de autonomia e liberdade quando se lança mão dessas atividades e manifestações.